FRI0529 Occupational Status of Patients with Childhood Onset Rheumatologic Diseases. (10th June 2014) - Quesada-Masachs, E.; Díaz-Mendoza, C.; Navarro-Cendejas, J.; Modesto, C.
Abstract : Objectives: To assess the labour market entry and the labour market performance of a cohort of patients followed in the transition program of a Pediatric Rheumatology Unit. Methods: A survey of patients followed in the transition program of a Pediatric Rheumatology Unit was conducted from September to December 2013. Data regarding demographic, clinical and labour status were collected: age, gender, diagnosis, disease onset, current treatment, family situation, educational attainment, occupational status and the patient's degree of difficulty to get a job and/or to perform it due to their illness. Descriptive and inferential statistics were used in the analysis of data. Labour data from our cohort were compared with those published in the 2012 Government Survey of Youth of Catalonia (GenCat). Results: The survey included 131 patients, 94 women (72%) and 37 men (28%). The mean age was 22 years (range 16-35). Juvenile Idiopathic Arthritis (JIA) represented the 52% (n=67) of the patients, Spondyloarthropathies (SpA) 19% (n=24), Autoinflammatory syndromes 8 (n=10) and other diseases 22% (n=28). The mean follow-up was 14±7.3 years. The percentage of patients on biological treatment was 32% (n=41). Regarding the family situation, 39% (n=38) were living alone, with classmates or in couple. Concerning the educational attainment, 18% had reached compulsory level, 38% post-compulsory secondary level and 43% higher education. The distribution of the major activity was 38% working and 50% studying. Unemployment was present in 11.5% of the sample. Regarding the difficulty to find a job due to their illness 70% answered that it didn't affect them at all. About the difficulty in performing their job 75% responded that they were unaffected. We could not establish a statistically significant relationship between the disease onset and the difficulty in achieving and/or performing a job, even though a trend of greater difficulty was observed in the group of longer disease onset (>15 years). Comparative data between our cohort and the general population of Catalonia is shown in Table 1 . It was observed that the rate of employment was comparable only among those individuals over 25 years of age, whereas in younger people there was an overrepresentation of students. The rate of unemployment of our cohort was similar to that found in the survey of Catalonia in all age groups (11.5% vs 10.4%). The number of individuals of our cohort who attainted post-compulsory secondary education and higher education was higher compared to the general population in Catalonia, 38.1% vs 29.2% and 43.3% vs 34.6% respectively. Conclusions: Our results show that among patients with childhood onset rheumatologic diseases there was no significant difficulty in finding and/or performing a job due to their illness. The percentage of individuals who attainted post-compulsory secondary and higher education studies was higher in our cohort compared to data obtained from the general population of the same age, while labour market entry occurs at a later age. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4751